Mechanical and Chemical Properties of Coal Bottom Ash as Sand and Cement Replacement: A review - mohamad adzali, Mohamad hazwan; Burhanudin, Mohd Khairy (Recent Trends in Civil Engineering and Built Environment, 2022)
Sand and cement are the main materials in the production of concrete, but it must deal with the problem of environmental issue related to the material resources. The goals of this study were to review mechanical and chemical properties CBA as sand and cement replacement in concrete. Plus, this review will justify the best percentage of CBA to be used in concrete as the sand and cement replacement. Some past studies have been conducted on the function of CBA as the replacement of sand and cement. The studies were done through literature review from different researchers. In this review, the characteristics of CBA were reviewed on mechanical and chemical properties from the previous published journal. From the review, coal bottom ash has shown that it was a right material to be the substitution of sand and cement in concrete. Besides, the ideal percentage of CBA as the replacement of sand and cement was 10% - 25%.